PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK FASE-E DI SMA NEGERI 8 PADANG - Puspita, Alvina Indah (Jurnal Edukasi dan Penelitian Matematika, 2023)
The main goal of the learning process is to improve students' ability to solve mathematical problems. However, the practice of problem solving skills among students in an educational environment is still inadequate. The Problem Based Learning model emerges as a potential undertaking by taking a unique approach to problem solving. In particular, the ability of E-phase students at SMAN 8 Padang to solve mathematical problems in the course material Equations and Quadratic Functions is the focus of this study, which seeks to determine the beneficial effects of the PBL model's adoption. This study adopts the quasi-experimental method and a quantitative methodology, as well as the research design posttest-only nonequivalent group design. There were 351 E-phase students at SMAN 8 Padang who made up the study's population. To select participants, the research sample selection strategy used a simple random sampling technique which was introduced as simple random sampling. As a result, X.E5 was designated as the experimental class, while X.E7 was designated as the control class. The results of the data analysis from the mathematical problem solving ability test, found a P-value of 0.002, with a significance level (α = 0.05). Because the P-value < α, the H0 implication is rejected. The study's findings support the hypothesis that utilizing a problem based learning paradigm has an impact or effect on E-Phase students enrolled in SMAN 8 Padang's capacity to solve mathematical problems.Keywords– Problem Based Learning (PBL) , Mathematical Problem Solving Ability